Recent Advances in C–F Bond Activation of Acyl Fluorides Directed toward Catalytic Transformation by Transition Metals, N-Heterocyclic Carbenes, or Phosphines - Tian, Tian; Chen, Qiang; Li, Zhiping; Nishihara, Yasushi (Synthesis, 2022)
Numerous studies on the activation of carbon–fluorine bonds have been reported in recent years. For example, acyl fluorides have been utilized as versatile reagents for acylation, arylation, and even fluorination. In this review, we focus on acyl fluorides as compounds with carbon–fluorine bonds, and highlight recent advances in strategies for the activation of their C–F bonds via transition-metal catalysis, N-heterocyclic carbene (NHCs) catalysis, organophosphine catalysis, and classical nucleophilic substitution reactions.1 Introduction2 Transition-Metal-Mediated C–F Bond Activation2.1 Acylation (Carbonyl-Retentive) Coupling Reactions2.2 Decarbonylative Reactions2.3 C–F Bond Activation by Other Transition Metals3 C–F Bond Activation by N-Heterocyclic Carbenes (NHCs)3.1 NHC-Catalyzed Cycloaddition of Acyl Fluorides3.2 NHC-Catalyzed Radical Functionalization of Acyl Fluorides3.3 NHC-Catalyzed Nucleophilic Fluorination of (Hetero)aromatics4 C–F Bond Activation by Phosphines4.1 Phosphine-Catalyzed Direct Activation of the C–F Bond of Acyl Fluorides4.2 Phosphine-Catalyzed Indirect Activation of the C–F Bond of Acyl Fluorides5 C–F Bond Activation by Classical Nucleophilic Substitution6 Miscellaneous Examples7 Summary and Perspective
Keywords: acyl fluorides; C–F bond activation; transition metals; N-heterocyclic carbenes; organophosphines